Distinctive Mechanisms of Adversity and Socioeconomic Inequality in Child Development: A Review and Recommendations for Evidence-Based Policy. (October 2017) - Amso, Dima; Lynn, Andrew
This review proposes separate and distinct biological mechanisms for the effects of adversity, more commonly experienced in poverty, and socioeconomic status (SES) on child development. Adversity affects brain and cognitive development through the biological stress response, which confers risk for pathology. Critically, we argue that a different mechanism, enrichment, shapes differences in brain and cognitive development across the SES spectrum. Distinguishing between adversity and SES allows for precise, evidence-based policy recommendations. We offer recommendations designed to ensure equity in children's experiences to help narrow the achievement gap and promote intergenerational mobility.